Depression in adolescent athletes: Prevalence and demographics - Long, A. S.; Price, D. E.; Bickett, A. K.; Hardeman, G. (Journal of Athletic Training, 2019)
Context: Depression prevalence and severity is increasing in the adolescent population. Estimates of depression in the general population of adolescents range from 4-18%. To our knowledge, no group has published the prevalence of depression in high school athletes, nor examined depression prevalence in various demographic categories. The emergence of depression screening on mandatory preparticipation examinations (PPE) provides an opportunity to examine the prevalence in an athletic population. Our purpose is to examine the rate of depression, as reported on the PPE, in an ethnically and socioeconomically diverse sample of secondary school athletes. Methods: We conducted a crosssectional, observational study using the PPE to determine depression prevalence in high school athletes participating in a station-based, largescale PPE. Our sample included athletes (N=2213, male=1,499 female=715) ages 13-18, (M=15.7 years) from both urban and suburban communities. Participants were provided transportation and a comprehensive PPE at no charge. Athletes, with parental consent and supervision, completed, electronically, a series of depressionrelated questions on the North Carolina High School Athletic Associations' PPE form. Measures included total number of students reporting depression on the PPE and demographics (age, gender, race, school Title I status, and sport). Results: Our fi ndings demonstrate 32 (1.4%) of our subjects reporting depression. African American females were the largest group, accounting for 30.3% of all depressed athletes in our sample. Female athletes were 1.9 times more likely to be depressed than males. Non-whites are over twice as likely to be depressed than whites. The sport played most frequently by the depressed group was football. There was a moderate correlation between each schools' total percentage of low income students and percentage of depressed athletes. (r=.41, P=.021). Conclusions: The prevalence of depression in our sample of high school athletes was below those previously reported in the general adolescent population. Females and non-whites had greater likelihoods of being depressed than males and whites. African American female high school athletes accounted for onethird of those depressed. Although exercise and sport participation have many benefi ts for mental health, health care providers should be vigilant when screening for depression in athletes, realizing that non-whites, females, and those at low-income schools may be more susceptible. Parental supervision may have liited accurate responses to depression questions. Future research will focus on responses in real time with the athlete only.